MANAGEMENT OF POTATO LATE BLIGHT (PHYTOPHTHORA INFESTANS) IN THE NILGIRIS - EP, Venkatasalam (Potato Journal, 2019)
ABSTRACT: Late blight caused by Phytophthora infestans (Mont.) de Bary is one of the most dreaded diseases of potato worldwide. In order to manage the disease, experiments were conducted to identify late blight resistant varieties, optimum date of planting and fungicides schedule. Among different varieties, Kufri Girdhari followed by Kufri Himalini were found to be resistant to late blight. Among different dates of planting, planting during the last week of April resulted in minimum AUDPC. Among different fungicide schedules, plots sprayed with mancozeb @ 0.2% as prophylactic spray and Azoxystrobin @ 0.1% as second spray or mancozeb @ 0.2% as prophylactic spray and Dimethomorph + mancozeb @ 0.3% as second spray and continuing the same sequence depending weather condition up to 75 days with the interval 7-10 days recorded minimum AUDPC, higher marketable yield as well as total tuber yield. For best management of late blight the susceptible variety could be planted during last week of April and resistant varieties during mid of May to first week of June.